Expression of Urea Transporter B in Normal and Injured Brain - Boyue Huang; Boyue Huang; Hongkai Wang; Hongkai Wang; Dandan Zhong; Jia Meng; Min Li; Baoxue Yang; Jianhua Ran (Frontiers Media S.A., 2021)
Urea transporter B (UT-B) is a membrane channel protein widely distributed in mammals, and plays a significant physiological role by regulating urea and water transportation in different tissues. More and more studies have found that UT-B is related to neurological diseases, including myelinopathy and depression. When urea accumulates in the brains of UT-B knockout mice, the synaptic plasticity of neurons is reduced, and the morphology and function of glial cells are also changed. However, the distribution and expression change of UT-B remain unclear. The purpose of this study is to determine the expression characteristics of UT-B in the brain. Through single-cell RNA sequencing, UT-B was found to express universally and substantially throughout the various cells in the central nervous system except for endothelial and smooth muscle cells. UT-B was detected in the third cerebral ventricular wall, granule cell layer of the dentate gyrus, and other parts of the hippocampal, cerebral cortex, substantia nigra, habenular, and lateral hypothalamic nucleus by immunohistochemistry. Compared with the membrane expression of UT-B in glial cells, the subcellular localization of UT-B is in the Golgi apparatus of neurons. Further, the expression of UT-B was regulated by osmotic pressure in vitro. In the experimental traumatic brain injury model (TBI), the number of UT-B positive neurons near the ipsilateral cerebral cortex increased first and then decreased over time, peaking at the 24 h. We inferred that change in UT-B expression after the TBI was an adaptation to changed urea levels. The experimental data suggest that the UT-B may be a potential target for the treatment of TBI and white matter edema.